Investigation of Mass Transfer of Ozone in Jet Loop Reactor - Cengiz, Ibrahim; Değermenci, Nejdet; Yildiz, Ergun; Barlak, Melahat Semin (Springer Science and Business Media LLC, 2024)
Mass transfer of ozone in a jet loop reactor was investigated in this study. Different parameters such as ozone gas concentration, gas flow rate, circulation flow rate, and spray nozzle diameter were examined for their effect on mass transfer. In experiments with ozone gas concentrations ranging from 3.83 to 17.1 g/m3, the KLa values remained unchanged, with an average of 28.7 +/- 2.2 h-1. As the ozone gas concentration increased, the saturation values of ozone in the liquid phase also increased. Experiments were carried out with gas flow rates ranging from 50 to 250 L/h in the jet loop reactor, and increasing gas flow rates increased the KLa value up to five times. When the effect of the liquid circulation flow rate was examined for a spray nozzle diameter of 15.5 mm, increasing the flow rate from 40 L/min to 80 L/min increased the KLa value by approximately 41%. However, the power consumed per reactor volume for this process increased 8 times and reached 2.65 kW/m3. KLa values in the JLR vary between 6.1 and 37.3 h-1 depending on operating parameters and it has been concluded that it performs well compared to its counterparts.
Keywords: Ozonation; Jet loop reactor; Ozone mass transfer